EFFECT OF MOTIVATION, DISCIPLINE, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE OF PT. NEW ASIA INTERNATIONAL IN SIDOARJO - Nur Afidatul Aliyah; Ony Kurniawati (Universitas 17 Agustus 1945 Surabaya, 2022)
The research is expected to see and examine the influence of motivation, discipline and work environment on employee performance at PT. New Asia International in Sidoarjo. The sample in this study were 50 workers or employees of PT. New Asia International in Sidoarjo, was taken using a purposive sampling strategy with the Slovin formula. This research method uses multiple linear regression. The results of this study indicate that motivation, discipline and work environment affect the performance of employees of PT. New Asia International in Sidoarjo is evidenced by the t-test, the significance value for the motivation variable is (X1) 0.028 <0.05 and the t arithmetic value > t table is 2.267 > 2.012. In the work discipline variable (X2), the significance value is 0.009 <0.05, and t count > t table 2.713 > 2.012. In the workplace variable (X3) the significance value is 0.000 <0.05 and t arithmetic > t table 4.801 > 2.012. This shows that each independent factor of motivation, discipline, and work environment partially affects the implementation of employee performance. Simultaneous results show that motivation, discipline and work environment simultaneously affect the performance of employees of PT. New Asia International in Sidoarjo with the results of the F test with a significance value of 0.000 < 0.05 and the calculated F value > F table that is 51.788 > 2.81. While the test results with the coefficient of determination (R2) indicate that motivation, discipline and work environment affect employee performance by 77.2% while the remaining 22.8% is influenced by various other variables.